Sepsis: A Brief Overview of the Key Concepts - P. G. Malkov; G. A. Frank (Общая реаниматология)
The issue of sepsis has been discussed extensively in the medical and scientific community for decades. However, a unified understanding of the biological nature of this condition has yet to be established.Aim. To provide a structured review of the key concepts commonly used in clinical practice and in the scientific literature related to sepsis.Materials and Methods. A review of the scientific literature combined with the authors' professional experience.Results. From a methodological perspective, it is suggested to conceptualize sepsis as a pathological condition due to generalized suppurative process. In this case, typical sepsis and septic shock are proposed to be considered two pathogenically separate, independently developing anatomo-clinical forms of sepsis.Conclusion. It is proposed to consider as sepsis only conditions associated with pathogens that are not capable of causing purulent inflammation. Non–purulent conditions not associated with pathogens of purulent infections are considered as generalization of bacterial, viral, protozoal, fungal diseases that may acquire toxic and especially toxic clinical forms designated as bacterial-toxic, or infectious-toxic (but not septic) shock. Typical sepsis and septic shock are proposed to be considered as independently developing clinical and anatomical forms of sepsis rather than the sequentially developing stages of the pathological condition.